Developing Bilingual Web-Based Information Center for Kampung Kemasan Gresik - Immanuela Corry Sri Hardani; Ririn Pratiwi Suharto; Novitasari Novitasari (INDO PUBLISHING, 2026)
Kampung Kemasan is a cultural heritage village located in Gresik, East Java, Indonesia, renowned for its historical atmosphere and distinctive architectural heritage that reflects multicultural influences of Dutch, Chinese, and Javanese traditions. Despite its tourism potential, Kampung Kemasan has limited digital promotion and online accessibility, making it less visible to potential visitors. This study aimed to develop a bilingual website as a centralized information center and promotional medium for Kampung Kemasan using Design and Development Research (DDR) adopted from Richey and Klein (2005) along with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through field observations, interviews with local stakeholders (Pokdarwis and Head Chief), and questionnaires from 114 respondents. The website was successfully deployed using a custom domain (https://www.kampung-kemasan.web.id/) in both Indonesian and English. Evaluations by language, IT/website, and content experts demonstrated high validity scores (96%, 92%, and 100% respectively), and field-testing results showed an overall success rate of 87.32% for local users and 91.71% for international users. The findings confirm that the web-based information center effectively enhances digital destination branding and information accessibility.